Catalase‐Loaded TaOx Nanoshells as Bio‐Nanoreactors Combining High‐Z Element and Enzyme Delivery for Enhancing Radiotherapy. Issue 33 (8th June 2016) - Song, Guosheng; Chen, Yuyan; Liang, Chao; Yi, Xuan; Liu, Jingjing; Sun, Xiaoqi; Shen, Sida; Yang, Kai; Liu, Zhuang
Abstract : A novel type of bio‐nanoreactor with catalase loaded inside TaOx hollow nanoshells is fabricated via a mild one‐step method. Such bio‐nanoreactors could efficiently improve the tumor oxygenation by supplying oxygen via decomposition of endogenic H2 O2 in a tumor microenvironment, and thus synergistically enhance the efficacy of cancer radiotherapy by both depositing radiation energy within the tumor and overcoming hypoxia‐induced radiotherapy resistance.